Reinforced Polymer Matrix Syntactic Foams Effect of Nano and Micro-Scale Reinforcement - Gupta, Nikhil; Pinisetty, Dinesh; Shunmugasamy, Vasanth Chakravarthy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Reinforced Syntactic Foams: Effect of Nano and Micro-Scale Reinforcement examines the fabrication processes, mechanism of reinforcement, and structure-property correlations of reinforced syntactic foams. The authors present the state of the art in this field, compare the properties of various types of syntactic foam systems comprising different matrix, hollow particle, and reinforcement materials. The book further identifies theories useful in predicting the properties of reinforced syntactic foams and conducting parametric studies to understand the possibility for tailoring their properties.
Introduction -- Fillers and Reinforcements -- Processing and MicroStructure of Syntactic Foams -- Tensile Properties -- Modeling and Simulation -- Compressive Properties -- Flexural Properties -- Fracture Toughness -- Dynamic Mechanical Properties -- Summary and Future Challenges.
Keywords: Ceramics; Glass; Composites (Materials).; Composite materials; Mechanics; Mechanics, Applied; Structural materials; Aerospace engineering; Astronautics; Ceramics, Glass, Composites, Natural Materials; Theoretical and Applied Mechanics; Structural Materials; Aerospace Technology and Astronautics